Crisis Management in the Tourism Industry-The Role of Social Media Platforms - Antony, Jose K; Jacob, Joel M (Atna Journal of Tourism Studies, 2021)
The tourism industry is highly susceptible to various forms of risks operating in the industry that occur and go unattended over a period of time. Social media could be effectively used to address the risks. Studies, however, on social media and its role in crisis management are few in spite of a consistent e mphasis on the importance of social media in the tourism industry, specifically, its role in crisis management. This paper provides a review of the current state of affairs and provides a framework to involve social media research in crisis management in tourism.